The impact of the COVID-19 pandemic on financial capacity of organizations: The sustainability challenges of social economy - Bonacho, C.; Santos, M. R. C.; Nunes, S.; Teixeira, N.; Dominguinhos, P.; Mata, C.; Mourato, J. (TMS ALGARVE 2022: Sustainability Challenges in Tourism, Hospitality and Management – Tourism & Management Studies International Conference, 2022)
More than a health crisis, the COVID-19 pandemic exposed the world to an economic and humanitarian crisis. All governments have faced difficulties in containing the spread of the virus, providing adequate healthcare and creating support measures for public and private institutions. Portugal was no exception and created packages of support measures, both financial and non-financial. But have these measures fit on the needs of all organizations? Were they enough for Social Economy organizations to maintain their activity at a time of increased demand? This study aims to determine the financial impact of the COVID-19 pandemic on Social Economy organizations, based on data collected through an online survey responded by 944 of those Portuguese organizations. The results show that, despite the measures implemented by the government, the Social Economy suffered an increase on expenses and a decrease on revenues during the second lock down imposed in 2021. A significant number of those organizations drastically reduced or even closed their activity. Several lessons learned are unveiled in this research, which may help Social Economy to be better prepared for future crises, namely the ones related to financial autonomy needed to be strengthen through the diversification of funding sources.